Legal Remedies Against the Excessive Remuneration of the Directors in Corporations Pursuant to Turkish Law - Esra Cenkci (Annales de la Faculté de Droit d’Istanbul)
The determination of directors’ remuneration under Turkish law can be determined in articles of incorporation or General Assembly. However, there is a lack of provisions specifying the principles governing the scope of corporation renumeration. This loophole poses the risk of transferring the corporation’s profits to the majority shareholders under the guise of remuneration, thereby violating minority shareholders’ rights. To address this challenge, courts have sought to balance directors’ entitlement to remuneration with shareholders’ rights to dividends through legal rulings. Remuneration paid to directors may be deemed illegal if they violate the shareholders’ rights to dividends. This study aims to determine the nature of such illegality and explore the legal remedies available to victimized shareholders. Furthermore, it examines the feasibility of reclaiming payments already disbursed to directors as a result of a resolution deemed illegal by the founding body.